Perkembangan Teori Pemerolehan Bahasa Pertama pada Anak Usia Dini dari Masa ke Masa: Sistematik Review - Mutahharah Nemin Kaharuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the development of first language acquisition theories in early childhood through a systematic review approach. By analyzing 52 scholarly publications from 2021 to 2025, the research identifies the theoretical evolution from behaviorist theories to modern neurobiological and computational approaches. The findings reveal that language acquisition theories have progressed from stimulus–response paradigms to a more comprehensive understanding of the interactions among genetic, neurological, and social-environmental factors. Key results highlight the emergence of new perspectives such as Dynamic Systems Theory, Usage-Based Theory reinforced by neuroimaging, and multimodal approaches to language acquisition. Practical implications include the development of more effective language learning strategies and early interventions for language disorders in children.